Diagnostic performance of HPV E6/E7 mRNA testing towards HPV‐DNA testing and p16/Ki67 immunostaining as a biomarker of high‐risk HPV recurrence in Greek women surgically treated for their cervical lesions. Issue 10 (9th August 2021) - Carcea, Fausto; Vavoulidis, Eleftherios; Petousis, Stamatios; Papandreou, Panagiotis; Siarkou, Chrysoula Margioula; Nasioutziki, Maria; Papanikolaou, Alexios; Dinas, Konstantinos; Daniilidis, Angelos
Abstract: Aim: To evaluate the diagnostic performance of E6/E7 HPV‐mRNA overexpression towards HPV‐DNA testing and p16/Ki67 immunocytochemistry in a post‐op population to verify if this biomarker can be effectively used as indicator of successful cervical intraepithelial neoplasia (CIN) treatment. Methods: Our study retrospectively analyzed 197 patients of our Colposcopy Clinic between January 2013 and September 2020 coming with an abnormal Pap smear suggestive for colposcopy, and after a series of follow‐ups including liquid‐based cytology (LBC) and punch‐biopsy sampling, there were surgically treated. LBC was used for cytology and molecular analysis of the three HPV‐related biomarkers. Results: Six months after treatment, 93% of the HPV‐mRNA‐positive women became negative while this applied to only 80.2% of the HPV‐DNA‐positive women. HPV persistence was 6.9% at 6–12 months after treatment. The comparison among cytology, colposcopy, HPV‐DNA test, and HPV‐mRNA test after treatment revealed that the last one is the only with a strong correlation with actual severity (histology during treatment) ( ρ = 0.345, p = 0.006) implying that clinical cases with more severe CIN may have higher chances of unsuccessful treatment. HPV‐mRNA test had higher sensitivity (100%), specificity (96.88%), and positive predictive value (45.45%) for CIN2+ recurrent lesions when compared with HPV‐DNA testing (80%, 82.81%, 10.81% respectively) and p16/Ki67 immunocytochemistry (80%, 95.83%, 33.33% respectively) while their negative predictive values were similar. Conclusions: E6/E7 mRNA detection has higher diagnostic values for the prediction of treatment failure compared with HPV‐DNA testing and p16/Ki67 immunocytochemistry, and as an outcome could be used as predictive indicator of CIN‐treatment status.